Effects of preheating temperatures on β‐lactoglobulin structure and binding interaction with dihydromyricetin. Issue 5 (8th September 2022) - Zhang, Wenyuan; Guan, Hui; Huang, Dongjie; Zou, Hui; Li, Dapeng
Abstract: Low aqueous solubility limits the bioactivity and bioaccessibility of dihydromyricetin (DHM). Preheating treatment affects the loading efficiency of β ‐lactoglobulin ( β ‐Lg) to polyphenols, but the mechanism remained unclear. In this study, a serial of temperatures (298 K, 318 K, 338 K, 358 K, and 373 K) were set to analyze the preheating effects on the loading efficiency of β ‐Lg to DHM, and secondary structure change, binding interactions, and particle size distribution were measured and compared with discover the effects. β ‐Lg preheated at 358 K possessed the highest binding percentage of 0.45, higher than 0.27, 0.30, 0.36, and 0.40 at 298 K, 318 K, 338 K, and 373 K, the exposure of inside hydrophobic residues contribute the hydrophobic interaction with DHM. Fluorescence quenching and molecular docking analysis showed that DHM tend to bind to β ‐Lg preheated at 358 K with a binding constant of 1.76 × 10 5 L mol −1 and a binding score of −5.84 kcal mol −1, higher than that of other temperatures. Particle size distribution showed that Z‐average size at 358 K was 16.34 nm, significantly higher than others of 7.64, 8.06, 6.84, and 13.4 nm. Preheating unfolded the structure of β ‐Lg, exposing the internal residues and enhancing the interaction with DHM. Abstract : Preheating treatment reduced the β‐sheets proportion of β‐lactoglobulin, increased the aggregation, and exposed the internal hydrophobic residues to form hydrophobic interactions with dihydromyricetin, leading to a higher binding affinity of dihydromyricetin at 358 K.